2006
DOI: 10.1007/s00417-006-0354-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative retinal break after 25-gauge transconjunctival sutureless vitrectomy: report of four cases

Abstract: Upon performing 25-gauge TSV for macular hole repair, care should be taken to detect retinal breaks and retinal detachment intraoperatively and postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 9 publications
2
15
1
Order By: Relevance
“…Also the vitreous incarceration at 1 sclerotomy did not induce a retinal break or retinal detachment. These data are comparable to Okuda et al [9], who observed retinal breaks in 5.3% of patients, or Ibarra et al [10], who reported retinal detachment in 2.2% of patients after 25-gauge transconjunctival vitrectomy. Sutures with a non-monofilament stitch could be a problem, particularly for infections.…”
Section: Discussionsupporting
confidence: 78%
“…Also the vitreous incarceration at 1 sclerotomy did not induce a retinal break or retinal detachment. These data are comparable to Okuda et al [9], who observed retinal breaks in 5.3% of patients, or Ibarra et al [10], who reported retinal detachment in 2.2% of patients after 25-gauge transconjunctival vitrectomy. Sutures with a non-monofilament stitch could be a problem, particularly for infections.…”
Section: Discussionsupporting
confidence: 78%
“…Vitreous incarceration in the sclerotomies could be responsible for anterior vitreoretinal traction. [24][25] We did not observe such complications in our series. The 23-gauge system permitted us to perform a more complete peripheral vitrectomy, with the help of better endo-illumination.…”
Section: Discussioncontrasting
confidence: 55%
“…[2][3][4][5][6][7] Reported complications include retinal break, retinal detachment, macular hole, cataract progression, hypotony, and breakage of the 25-gauge cutter within the eye. 2,[8][9][10] More concerning, several reports have suggested that the 25-gauge system may result in an increased incidence of postoperative endophthalmitis, [11][12][13][14][15] which can lead to significant morbidity as potential sequelae include irreversible loss of vision. The purpose of this study was to estimate the incidence of endophthalmitis after sutureless 25-gauge vitrectomy surgery and to determine whether there was an increased risk of infection after 25-gauge vitrectomy compared to traditional 20-gauge vitrectomy.…”
Section: Introductionmentioning
confidence: 99%